Breast Cancer Imaging and Therapy - Seely, Jean (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In Canada, survival from breast cancer has steadily increased since 1989, and breast cancer mortality has decreased by 48%. While 82% of women with breast cancer are diagnosed at stage 1 or 2, there are still 18% who present at a late stage and 25% who develop metastatic disease. Improved survival has been achieved through early diagnosis of breast cancer with screening, allowing for more effective and targeted treatments. This reprint summarizes the latest evidence on the early detection of breast cancer and highlights areas where this may be improved.